2020
DOI: 10.1111/eci.13251
|View full text |Cite
|
Sign up to set email alerts
|

The impact of subclinical congestion on the outcome of patients undergoing transcatheter aortic valve implantation

Abstract: Background We investigated the impact of an elevated plasma volume status (PVS) in patients undergoing TAVI on early clinical safety and mortality and assessed the prognostic utility of PVS for outcome prediction. Materials and methods We retrospectively calculated the PVS in 652 patients undergoing TAVI between 2009 and 2018 at two centres. They were then categorized into two groups depending on their preoperative PVS (PVS ≤−4; n = 257 vs PVS>−4; n = 379). Relative PVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In a cohort of 652 TAVI patients, PVS ≥4 was associated with all-cause mortality in the longer term and was associated with a 30-day composite of all-cause mortality, stroke, life-threatening bleeding, acute kidney injury, coronary artery obstruction requiring intervention, major vascular complication and valve related dysfunction requiring repeat procedure. 22 However, PVS ≥4 was not associated with the primary endpoint for that study, 22 that is, 30-day mortality, and until now the findings have not undergone external validation in an independent cohort. Our study builds on previous data, by independently validating the association between elevated PVS and mortality, and showing that PVS >0% is associated with prolonged ICU stay.…”
Section: Discussionmentioning
confidence: 83%
“…In a cohort of 652 TAVI patients, PVS ≥4 was associated with all-cause mortality in the longer term and was associated with a 30-day composite of all-cause mortality, stroke, life-threatening bleeding, acute kidney injury, coronary artery obstruction requiring intervention, major vascular complication and valve related dysfunction requiring repeat procedure. 22 However, PVS ≥4 was not associated with the primary endpoint for that study, 22 that is, 30-day mortality, and until now the findings have not undergone external validation in an independent cohort. Our study builds on previous data, by independently validating the association between elevated PVS and mortality, and showing that PVS >0% is associated with prolonged ICU stay.…”
Section: Discussionmentioning
confidence: 83%
“…This accuracy was validated by comparing scintigraphy tests, 7,8 with prognostic implication on heart failure recurrence and mortality also demonstrated in prior published studies 7,8 . PV additionally has been shown to predict clinical risk in several clinical settings other than heart failure, including transcatheter aortic valve replacement and coronary artery bypass grafting registries 9,10 …”
Section: Discussionmentioning
confidence: 74%
“…Recently, a novel procedure to noninvasively estimate plasma volume (PV) simply using hematocrit (Ht) and body weight (BW), has been proposed 6 . This specific accuracy was validated using scintigraphy tests, 7,8 and its prognostic implication in heart failure cohorts was demonstrated in several clinical settings 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…In line with findings in the known literature, 32.1% of patients in our cohort presented in a preoperative state of (subclinical) decompensation represented by a PVS above the defined cut-off level similar to those presented in recent studies. [ 6 , 7 , 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has demonstrated that plasma volume status (PVS) can be calculated easily based on the patients’ weight, gender and hematocrit [ 7 ]. Furthermore, an elevated PVS is known to directly correlate with increased mortality in patients with stable CHF, and has been applied for risk stratification in patients undergoing coronary artery bypass graft surgery or transcatheter aortic valve replacement [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%